تقدير أثر مكونات الهيكل السلعي للتجارة الخارجية في النمو الاقتصادي لتركيا للمدة (1990-2009) - الكواز، سعد محمود خليل; داؤد، أكرم حنا (جامعة الموصل - مركز الدراسات الإقليمية, 2013)
بينت العديد من الدراسات الاقتصادية أن لمتغيرات هيكل التجارة الخارجية (الصادرات والاستيرادات)ذات أثر في الناتج المحلي الإجمالي وتحريك النمو الاقتصادي لدولة ما، وخاصة تجارة السلع الصناعية لأنها تسهم في إنتاج القيمة المضافة، وأهميتها للدول المتقدمة والنامية، والاستفادة منها في عملية التنمية الاقتصادية، يهدف البحث إلى التعرف على مكونات الهيكل السلعي للتجارة الخارجية التركية وتوضيح تأثيرها في الناتج المحلي الإجمالي لسلسلة زمنية هي عشرون سنة. \ \ ومن أجل تحقيق الهدف، فقد استندت الفرضية على أن لمكونات الهيكل السلعي للصادرات والاستيرادات لتركيا تأثيرًا واضحًا في الناتج المحلي الإجمالي، وإن الجهود التي تبذلها تركيا للانضمام إلى الاتحاد الأوربي أدت إلى حدوث تغير في اتجاهات التجارة الخارجية التركية، ولغرض الوصول إلى هدف البحث وإثبات فرضيته، فقد أجريت الدراسة باستخدام المنهج الكمي، وذلك بالتعرف على ملامح تطور الاقتصاد التركي، وتصنيف الهيكل السلعي للتجارة الخارجية وعلاقته بالنمو الاقتصادي، كما تم تحليل اتجاهات تطور التجارة الخارجية التركية للمدة (1990- 2009) واتجاهات تطور مكونات الهيكل السلعي للصادرات والاستيرادات التركية، فضلاً عن اتجاهات التوزيع الجغرافي للتجارة الخارجية لتركيا لخلال مدة الدراسة. \ \ توصلت الدراسة إلى أن السلع الوسيطة والاستهلاكية أهم الفقرات في الهيكل السلعي للصادرات التركية خلال مدة الدراسة، فضلاً عن السلع الرأسمالية والسلع الأخرى، في حين كانت السلع الوسيطة والرأسمالية أهم الفقرات في الهيكل السلعي للاستيرادات, فضلاً عن السلع الاستهلاكية والسلع الأخرى. Showed many of the economic studies that the variables structure of foreign trade (exports and imports) with the impact of the gross domestic product and move the economic growth of a State‘ and private trade in industrial goods because they contribute to value- added production, and its importance to developed and developing countries, and take advantage of the economic development process, aimed at search to identify the components of Commodity Structure of Foreign Trade of Turkey and to clarify their impact on the GDP time series is twenty years old. In order to achieve the goal, was based on the assumption that the components of the structure of commodity exports and imports of Turkey to influence evident in the GDP, and the efforts made by Turkey to join the European Union led to a change in the directions of Turkish foreign trade, in order to reach the goal of the research and prove his hypothesis, The study was conducted using a quantitative methodology, by identifying the features of the evolution of the Turkish economy, and classification of Commodity Structure of Foreign Trade and its relationship to economic growth, were also analyzed trends in the evolution of Turkish foreign trade for the period (1990-2009) and the development trends of components of the structure of commodity exports and imports of Turkey, as well as trends geographical distribution of foreign trade of Turkey during the study period. \ The study found that intermediate and consumer goods the most important paragraphs in the Commodity Structure of Turkish exports during the period of study, as well as capital goods and other commodities, while the intermediate and capital goods the most important paragraphs in the Commodity Structure of imports, as well as consumer goods and other goods.
Keywords: تركيا -- التجارة الخارجية -- الهيكل السلعي -- التنمية الاقتصادية